Retos en la enseñanza de un niño con autismo de 2do de egb en la unidad educativa Jesús de Nazaret, 2025 - Armijos Romero, Angel Amable (2025)
Autism is a complex disorder that brings with it affectations in communication and social interaction, which generate challenges in the learning of the student who presents this condition of grade 2, to this the inclusion is an important factor in the adaptation to the educational environment of the child, for this reason the objective of: Analyze the educational inclusion of a child with autism spectrum disorder (ASD) of 2nd EGB in the U.E Jesus de Nazareth, in order to achieve the purpose, the methodology applied consists with a qualitative approach and a field research design with case study type, where the challenges that arise in the learning of a child with ASD are observed and theoretically founded that strategies are appropriate for inclusion and adaptation of the student's education. In addition, this study tends to be descriptive, where the variables on autism spectrum disorder and educational inclusion are deepened, which allowed us to learn about the history, diagnoses, teaching and learning strategies for children with autism. This research is a path towards full inclusion for students with special educational needs associated with disability, where the most important aspects for the student's academic development are reflected.